2020
DOI: 10.1103/physrevd.102.055023
|View full text |Cite
|
Sign up to set email alerts
|

Probing new physics in semileptonic Σb and Ωb decays

Abstract: Recently, several hints of lepton nonuniversality have been observed in the semileptonic B meson decays in terms of both in the neutral current (b → sll) and charged current (b → clν l) transitions. Motivated by these inspiring results, we perform the analysis of the baryon decays Σ b → Σ c lν l and Ω b → Ω c lν l ðl ¼ e; μ; τÞ which are mediated by b → clν l transitions at the quark level, to scrutinize the nature of new physics (NP) in the model independent method. We first use the experimental measurements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
2
1
0
Order By: Relevance
“…For Ω b → Ω c lν l decay, we only consider the effect of the aforementioned four NP models in this work. The SM central values of various observables for this process have been given in our previous work [79]. By comparing our results with those of [79], it is found that the P τ L of Ω b → Ω c τ ντ is positive, while all the P l L for the Ξ b → Ξ c lν l process are negative.…”
Section: Numerical Analysis and Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…For Ω b → Ω c lν l decay, we only consider the effect of the aforementioned four NP models in this work. The SM central values of various observables for this process have been given in our previous work [79]. By comparing our results with those of [79], it is found that the P τ L of Ω b → Ω c τ ντ is positive, while all the P l L for the Ξ b → Ξ c lν l process are negative.…”
Section: Numerical Analysis and Discussionsupporting
confidence: 55%
“…The SM central values of various observables for this process have been given in our previous work [79]. By comparing our results with those of [79], it is found that the P τ L of Ω b → Ω c τ ντ is positive, while all the P l L for the Ξ b → Ξ c lν l process are negative. Furthermore, all the P Ω c L are positive, while the P Ξ c L are negative.…”
Section: Numerical Analysis and Discussionsupporting
confidence: 55%
See 1 more Smart Citation